PENGARUH PERMAINAN TARGET TERHADAP HASIL SERVIS FOREHAND PANJANG BULUTANGKIS - Firyaal Safiinatunnajah, - (2022)
The problem in this study is the lack of ability of athletes to perform long forehand service techniques so that many mistakes occur when playing in the field. Because athletes have not been able to master these basic techniques and lack of routine practice on the basic techniques of long forehand serve. This study attempts to analyze the effect of target play on the long forehand serve of badminton. The method used is a quasi-experimental method. The population in this study is PB.SFBC Sumedang. Data collection method using long forehand service test. The data analysis technique was carried out using an independent simple t-test using the SPSS for windows 20 application. At the t-test level, the sig value was significant. (2-tailed) < 0.05. Based on the results of data analysis, this study shows that there is an effect of target training on the results of the badminton long forehand serve with the value obtained by Sig. 0.000 < (a = 0.05) then H1 is accepted. So it can be concluded that the target game has an effect on the results of the badminton long forehand serve.